An Economic Study of The Competitiveness of Egyptian Grape Exports in its Most Important World Markets - Hamza, Yasser T. A.; Elsayed, Elham A. A.; Meky, Fouaad M. H. (Advances in Social Sciences Research Journal, 2023)
The research aims to study the Egyptian grape exports in terms of their temporal stability and geographical distribution, as well as reviewing the most important competing countries for Egypt. It also aims to measure competitive indicators of Egyptian grape exports in its most important global markets, and to compare these indicators, in order to reach some proposals to increase competitiveness and the possibility of developing its exports in the future in those markets on the one hand, and to open new markets on the other hand. The study relied on the two methods of descriptive and quantitative analysis, as well as some methods of statistical analysis to measure economic relations during the period (2000-2020). The competitiveness of Egyptian grape exports in its most important global markets was measured using four indicators: apparent competitive advantage, price competitiveness, market share, and market penetration rate. This is in addition to the comparison between the third and fourth indicators during the period (2016-2020). The most important findings of the study can be summarized as follows: The existence of a large fluctuation and the promise of stability in each of the quantity, value and export price of Egyptian grapes, as the stability coefficient for them was estimated at 11.29%, 43.18%, and 27.15%, respectively, as an average for the period (2016-2020). The annual increase in domestic production amounted to the amount of Egyptian grape exports at about 14.32, 7.17 thousand tons, i.e. an annual growth rate estimated at 1.73% and 8.86%. The annual increase in the value and export price of Egyptian grapes amounted to about $15.06 million, or $102.58/ton. That is, an annual growth rate estimated at 10.67% and 7.02%, respectively. This increase has been statistically significant during the same period. There are many global markets for Egyptian grape exports, but the most important ones are represented in three main markets: the European Union, the Arab countries, and the African countries. This is in addition to some other countries’ markets, where Egypt’s total grape exports amounted to about 118.16 thousand tons, representing about 91.98% of the total amount of Egyptian grape exports amounting to about 128.46 thousand tons, with a value of $1080.76 million, representing about 94.11% of the total value. Egypt's grape exports amounted to about $1,148.40 million during the same period. The most important countries competing for Egyptian grape exports are: Chile, Italy, Peru, America, South Africa, the Netherlands, Turkey, Hong Kong, India, Spain, Afghanistan and Uzbekistan, as their total exports amount to about 3900.6 thousand tons, representing About 86.11% of the world's total exports amounting to about 4768.0 thousand tons during the same period. Chile ranked first in world grape exports, with a quantity of about 768.6 thousand tons, representing about 16.1%, while Egypt ranked twelfth with a quantity of exports amounting to about 128.5 thousand tons, representing about 2.7%, representing about 16.1% of the total amount of world grape exports. amounting to about 4,768 thousand tons during the same period. Egypt enjoys price competitiveness when compared to the following countries: America, China, Peru, the Netherlands, Spain, Hong Kong, Australia, where the average export price for these countries was about 2300.1, 2674.5, 2355.2, 2536.3, 2273.9, 1811.6, 2724.4 dollars/ tons, representing about 77.7%, 66.8%, 75.9%, 70.4%, 78.6%, 98.6%, and 65.1% for those countries, respectively, of the average export price of Egyptian grapes, which amounted to about $1786.8 / ton during the same period. The existence of high export capabilities to increase the Egyptian grape exports to the markets of Arab countries, especially: UAE, Saudi Arabia and Kuwait. As well as the markets of the European Union countries, especially: Germany, Italy, the Netherlands, the United Kingdom. And also the markets of African countries, especially: South Africa, Kenya. Based on the findings of the study, it recommends the following: The need to reduce production, marketing and manufacturing costs. This leads to a decrease in the export prices of Egyptian grapes compared to those of competing countries, especially: Chile, Italy, South Africa, Turkey, India, Uzbekistan and Greece. Increasing Egyptian grape exports through increasing the market share, market penetration rate, especially in Arab countries such as: UAE, Saudi Arabia, Kuwait, Oman, as well as European Union markets such as: Germany, Holland, Italy, and the United Kingdom., as well as the markets of African countries such as: South Africa, Kenya, Nigeria, which are promising new markets. This is due to the presence of high export potential, as its markets can accommodate more Egyptian grapes. Preserving the traditional markets for Egyptian grape exports, in terms of preserving its import capacity and increasing its market share, especially the markets of Arab countries such as: UAE, Saudi Arabia, as well as European Union countries such as: The United Kingdom, the Netherlands, and also African countries in particular: South Africa, Nigeria, Kenya. This is due to the presence of some export potentials of Egyptian grapes in those markets.